Student’s Social Moral in Adolescent Psychological Development - Ainissyifa, Hilda; Fauzi Ridwan, Fauzi (International Journal of Engineering and Technology, 2018)
Education in adolescence period is one of the important bases in studentsâ€™ moral building. In education process, studentâ€™s behavior is allegedly influenced by the development of adolescent psychology. This study aims to reveal the influence of adolescent psychological development to studentâ€™s social moral. The method used in this research is a quantitative method with statistical descriptive and inferential approach. The research data are taken based on the occurring phenomenon and drawing conclusion from the data of sample result by t-test. This study involves 41 students as respondents, and the research site is Vocational School (SMK) of Al-Mukhtariyah, Cinisti Village, Bayongbong sub-district, Garut, Indonesia. The research finding showed that the variable reality of adolescent psychological development and studentsâ€™ association moral are seen to have quite well criteria. The correlation between adolescent psychological development variable and studentsâ€™ social moral is in the high category. According to the result of a significance test, the study stated that adolescent psychological development has significant positive effect on studentsâ€™ social moral. The study recommends a holistic form of education, which does not only apply moral education at school. Moral education needs to get more attention from all parties such as school, society, parents, and government. Â